Myoepithelioma of the upper lip - Hirohiko Tachibana; Shigeo Ishikawa; Noriaki Kikuchi; Mitsunori Yamakawa; Yoshioki Hamamoto; Mitsuyoshi Iino (Elsevier, 2017)
Myoepithelioma is a rare form of salivary gland tumor composed entirely of myoepithelial cells. This tumor was formerly considered to be a subtype of pleomorphic adenoma; however, in the 1991 World Health Organization classification, it is listed as an independent entity. The most favorable site of occurrence of myoepithelioma is the parotid gland. Here, we report an extremely rare case of myoepithelioma of the upper lip. A 56-year-old woman presented with a painless mass on her upper lip. Magnetic resonance imaging revealed a 23 mm × 18 mm well-defined ovoid tumor. A benign minor salivary gland tumor was clinically suspected, and the patient underwent complete resection of the tumor under general anesthesia. The tumor was histopathologically diagnosed as a benign myoepithelioma of the minor salivary gland. Immunohistochemically, the tumor cells were positive for S-100 protein, AE1/AE3, CAM5.2, CK7, vimentin, and calponin, confirming the morphologic diagnosis of myoepithelioma. The patient's postoperative clinical course was uneventful, and satisfactory results were obtained both functionally and esthetically. To the best of our knowledge, this is the sixth case of myoepithelioma of the upper lip reported in English-language research.